Cognitive and motor abilities predict auditory-cued finger tapping in a dual task - Mudarris, Mohammed A.; Krijt, Renske N.; Hassell, Allyah M.; Murphy, Tanya M.; Ruitenberg, Marit F. L.; Fokkema, Marjolein; Schaefer, Rebecca S. (Frontiers in Neuroscience, 2025)
Rhythmic auditory stimulation, a therapeutic method involving repetitive movements cued by rhythmic sounds, can support movement (re-)learning and attentional orienting, but effects vary. While properties of cues have been extensively studied, not much is known about the impact of individual differences in cognitive and motor abilities that enable sensorimotor synchronization. This study examined how stimulus complexity (metronome/music) and cognitive and motor functions affect tapping timing consistency and force. Fifty healthy young adults (ages 18–39) performed several finger tapping tasks, specifically, as a stand-alone task (single task), and simultaneously with 2-Back working memory task (dual task), each to sounds with a clear, steady beat and differing levels of rhythmic complexity (metronome vs. music). Standardized neuropsychological tests were related to consistency and force in the single task and to their dual task cost (interference). The dual task led to lower tapping consistency for both auditory cues. Poorer cognitive inhibition and better gross motor ability each predicted greater applied force. In contrast, participants with poorer fine motor ability tapped with lower force. Accounting for musical training and reward from music revealed that sustained attention, verbal memory, musical training and reward additionally predicted tapping force, whereas only musical training predicted better tapping consistency. These non-linear relationships were shown for both single and dual tasks, but not for the dual task cost. Overall, this study highlights the complex interactions of movement functions and cognitive abilities with sensorimotor synchronization, essential to many music-based interventions, and underlines the importance of the consideration of individual baseline abilities.